NANOSUSPENSIONS: A STRATERGY TO INCREASE THE SOLUBILITY AND BIOAVAILABILITY OF POORLY WATER-SOLUBLE DRUGS - Jakka, Vidyadhari; GAYATRIRAMYAMUNAGALA,; PATNALA, DURGA SPVN PAVANI; Kuruba, Rajesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
The process that occurs at the molecular level and at the nanoscale is the subject of nanotechnology. Nanotechnology includes nanosuspension. Nanosuspension is a colloidal dispersion of medication particles that are nanometer-sized and stabilized with surfactants. To manufacture and scale up nanosuspensions, conventional size reduction tools such as media mills and high-pressure homogenizers as well as formulation strategies including precipitation, emulsion-solvent evaporation, solvent diffusion, and microemulsion procedures can be successfully used. The main elements to be taken into consideration for the effective manufacture and scale-up of nanosuspensions are maintaining the stability in solution as well as in the solid form, and resuspendability without aggregation. The flexibility for surface modification and mucoadhesion for drug targeting have substantially broadened the scope of this innovative formulation method as a result of the significant improvement in bioavailability. Extensive research is now being done on the use of nanosuspensions in various drug delivery methods, including oral, ophthalmic, brain, topical, buccal, nasal, and transdermal routes. The majority of permeability limiting absorption and hepatic first-pass metabolism associated difficulties that negatively affect bioavailability can be resolved with oral drug delivery of nanosuspension with receptor mediated endocytosis, which is a promising capability. The development of enabling technologies like nanosuspension can address several formulation issues that protein- and peptide-based medicines currently encounter